Implementasi Manajemen Keuangan Yayasan Guna Menghasilkan Pendidikan Yang Bermutu (Yayasan Sayap Ibu Banten) - Hendri Gunawan; Vega Anismadiyah; Vidya Amalia Rismanty (Universitas Pamulang, 2022)
This Community Service is entitled Implementation of Foundation Financial Management to Get Qualified Education. The activity was carried out at the Yayasan Sayap Ibu Banten from May to June 2022. In improving the quality of education, teachers have a very important position and strategy in developing the potential of students. Teachers play a big role in the glory and safety of the nation’s future through inculcating noble basic values as the ideals of national education by forming a physically and spiritually prosperous personality, which is pursued through religious education and general education. The purpose of carrying out community service activities is to provide counseling, assistance and a question and answer process on the importance of implementing Foundation Financial Management to Produce Qualified Education. The method of community service activities consists of three stages of activity. The first stage is the preparation stage in conducting a survey of partner locations, activity participants and preparing materials. The second stage is the implementation which includes giving lectures on the implementation of Foundation Financial Management to Produce Quality Education. The third stage is evaluation, among others, to find out how deep the understanding of the training participants to the material provided. The conclusion of this community service activity is that the Owners, Leaders, Management and Teachers of the Yayasan Sayap Ibu Banten are enthusiastic in accepting new knowledge and actively asking questions about how to implement the Foundation's Financial Management to Produce Qualified Education.